10th ADCE European Creativity Festival - Panayides, Angelos (My University, 2026)
ADCE Festival 2023 Topic - Agents of Change Curated by Wesley ter Haar, Co-founder of MediaMonks Agents of change, or are they agents of chaos? Creatives can be heralded as the first, by us and others, and sometimes derided for being the latter. But when years of news and new realizations get crammed into mere months, and science fiction steadily and sneakily turns into just science (or is it sentience), change itself starts to feel chaotic. It might be life’s only constant, but we don’t talk enough about the inconsistency of change. How it shocks systems, roils and revolutionizes industries, exhilarates some but induces anxiety in most, how it can make the future feel like it’s already happening, just slightly outside of view. This year we’ll be celebrating agents of change, those within our industry and from elsewhere, and how they’ve managed to control or even cajole the chaos to deliver change, in their work, in their industry, and beyond. Each edition of the ADCE Festival strives to present innovative ideas and models that challenge the way we see creativity and inspire shifts in perceptions that will help reshape the future of the industry. As a curated event, participants are exposed to meaningful talks revolving around a major chosen topic of specific relevance to the fields of design and advertising. Most of the speakers go on to work hand-in-hand with the participants in one of the programmed workshops covering industry trends, new technologies and powerful working models. All in all, attendees walk away with new ideas that can make a real impact on their work.